Impactul psihologic al pandemiei Covid-19 asupra studenților din cadrul Universității Babeș-Bolyai - Daniela Cotoranu; Simona Claudia Creța; Octavian Moldovan (Revista Transilvană de Ştiinţe Administrative, 2021)
The Covid-19 pandemic has generated a number of changes in higher education, regarding both students and professors who had to adapt to online teaching and the challenges brought by this new educational paradigm. The current research analyzes the impact of the Covid-19 pandemic on students at Babeș-Bolyai University from Cluj-Napoca, by identifying their level of anxiety. The research results showed an average level of anxiety among respondents, with slight differences in the level of anxiety depending on age (younger students having a higher level of anxiety) and gender (female students being more likely to develop anxiety), the results indicating a high level of stress, nervousness and difficulties in controlling the situation among students. The Covid-19 pandemic caused new concerns among respondents about how to take the final exams, the impossibility of returning to college in physical format, the prospects for employment in the near future, but also about the fact that their grades may be affected. The Covid-19 pandemic had a negative psychological impact on most students participating in the study regardless of the specialization in which they are enrolled.